A Peptide Antagonist of Thrombospondin-1 Promotes Abdominal Aortic Aneurysm Progression in the Angiotensin II–Infused Apolipoprotein-E–Deficient Mouse. Issue 2 (February 2015) - Krishna, Smriti M.; Seto, Sai Wang; Jose, Roby J.; Biros, Erik; Moran, Corey S.; Wang, Yutang; Clancy, Paula; Golledge, Jonathan
Abstract : Objective—: Interaction of the activating sequence in thrombospondin-1 (TSP-1) with the conserved sequence (leucine-serine-lysine-leucine [LSKL]) in the latency-associated peptide region of latent transforming growth factor (TGF)-β complex is important in regulating TGF-β1 activity. We aimed to assess the effect of blocking peptide LSKL on the progression of pre-established abdominal aortic aneurysm in angiotensin II–infused apolipoprotein E-deficient (ApoE −/− ) mice. Approach and Results—: Abdominal aortic aneurysm was established in 3-month-old male ApoE −/− mice with subcutaneous infusion of angiotensin II for 28 days. After this, mice received LSKL peptide or control SLLK (serine–leucine–leucine–lysine) peptide (4 mg/kg) via daily intraperitoneal injection for an additional 2 weeks. Administration of LSKL peptide promoted larger suprarenal aortic diameter, as determined by ultrasound and morphometric analysis, and stimulated more severe atherosclerosis within the aortic arch. In addition, mice receiving LSKL peptide exhibited elevated circulating proinflammatory cytokine levels and greater inflammatory cells within the suprarenal aorta compared with controls. Mice receiving LSKL peptide showed low plasma TGF-β1 activity and low levels of aortic tissue phosphorylated to total Smad2/3. Aortic gene expression of TGF-β receptor 1 ( TGFBRI ) and receptor 2 ( TGFBRII ), but not TGF-β1 and thrombospondin-1, were lower in mice receiving LSKL peptide than controls. LSKL peptide administration was associated with greater aortic elastin fragmentation and lower expression and activity of the TGF-β1-target gene lysyl oxidase like 1 ( LOXL1 ). Conclusions—: Attenuation of thrombospondin-1-directed activation of TGF-β1 promotes abdominal aortic aneurysm and atherosclerosis progression in the angiotensin II–infused ApoE −/− mouse model. Abstract : Supplemental Digital Content is available in the text.